2021
DOI: 10.1037/dev0000976
|View full text |Cite
|
Sign up to set email alerts
|

Developmental profiles of reading fluency and reading comprehension from grades 1 to 9 and their early identification.

Abstract: This study examined developmental profiles of reading fluency and reading comprehension in Grades 1 to 9 (ages 7 to 15) in a large Finnish sample (N = 2,518). In addition, early predictors of the profiles were analyzed with respect to kindergarten cognitive skills (phonological awareness, letter knowledge, rapid automized naming [RAN], number counting, word reading, vocabulary, and listening comprehension), parental factors (level of education, reading difficulties), and gender. Four different profiles of read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 73 publications
(213 reference statements)
6
25
0
Order By: Relevance
“…Regarding the between-person association, that is, the question of whether children with good silent reading fluency skills have better reading comprehension skills than children with poor silent reading fluency skills, the model strongly indicated that silent reading fluency and reading comprehension are positively associated with one another. This finding supports many previous studies (e.g., Florit & Cain, 2011;Kershaw & Schatschneider, 2012;Lonigan et al, 2018;Psyridou et al, 2021;Santos et al, 2020;Torppa et al, 2016). Our results add to the previous literature by showing that the associations between the two skills exist but seem to diminish across Grades 1-9.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the between-person association, that is, the question of whether children with good silent reading fluency skills have better reading comprehension skills than children with poor silent reading fluency skills, the model strongly indicated that silent reading fluency and reading comprehension are positively associated with one another. This finding supports many previous studies (e.g., Florit & Cain, 2011;Kershaw & Schatschneider, 2012;Lonigan et al, 2018;Psyridou et al, 2021;Santos et al, 2020;Torppa et al, 2016). Our results add to the previous literature by showing that the associations between the two skills exist but seem to diminish across Grades 1-9.…”
Section: Discussionsupporting
confidence: 92%
“…Based on previous research, we expect that silent reading fluency and reading comprehension will be associated at the between level since previous studies both in English and in Finnish have shown that children with good performance in one skill tend to have good performance also at the other (e.g., Nation, 2019;Psyridou et al, 2021). Regarding the association at the within level, we expect to find bidirectional effects between the two skills (e.g., Carretti et al, 2020;Kershaw & Schatschneider, 2012;Little et al, 2017;Santos et al, 2020;Torppa et al, 2016).…”
Section: The Present Studymentioning
confidence: 86%
“…In the present study, the kindergarten prereading measures do not seem to fully explain the gender differences in reading fluency either. Interestingly, rapid naming, which is known to be a strong predictor of reading fluency development (e.g., Georgiou et al, 2008;Psyridou et al, 2021;Savage & Frederickson, 2005), showed a very small gender difference with only a negligible effect size.…”
Section: Discussionmentioning
confidence: 99%
“…These results contrast those of Torppa et al (2007), who observed a poor comprehender group in a different sample of Finnish readers earlier in schooling (Grades 1-2). Although the evidence is mixed (Psyridou et al, 2021), we tentatively consider that development may also be important to understanding these conflicting findings. Foorman et al (2017) found evidence of qualitatively distinct literacy profiles in early school grades, yet only ordered profiles emerged beyond 5 th grade.…”
Section: Lack Of Support For Categorical Profiles Based On the Simple...mentioning
confidence: 91%
“…Thus, it remains plausible that the hypothesised profiles would have emerged if entirely separate assessments of decoding and comprehension were used. However, these component skills are highly correlated in developing readers of this age (see García & Cain, 2014, for a meta-analysis), and a recent study of Finnish readers also failed to identify discrepant profiles despite using measures from different tasks (Psyridou et al, 2021). These results contrast those of Torppa et al (2007), who observed a poor comprehender group in a different sample of Finnish readers earlier in schooling (Grades 1-2).…”
Section: Lack Of Support For Categorical Profiles Based On the Simple...mentioning
confidence: 98%